A note on exponentiated generalized inverse Pareto distribution - Ogunde*, A.A.; Oseghale†, O.I.; Fatoki‡, O. (International Journal of Mathematical Analysis and Modelling, 2023)
The Exponentiated Generalized inverse Pareto (EGIP) distribution is derived using Exponentiated-G generator which introduces additional two new parameters into the inverse Pareto model. Some basic statistical properties of the model are derived which includes: moment and incomplete moment, moment generating function, quantile function, Renyi and